Socioeconomic, Spatial, and Infrastructural Determinants of Health among Single Older Women: A Descriptive Analysis - Bratanegara, Alnidi Safarach; Pitoyo, Agus Joko; Widayani, Prima; Hizbaron, Dyah Rahmawati; Perdani, Agni Laili; Koa, Apryadno Jose Al Freadman (Jurnal Pendidikan Keperawatan Indonesia, 2025)
Introduction: The aging population presents significant global challenges, especially in developing countries such as Indonesia. In West Java Province, Tasikmalaya Regency has the highest number of single female elderly, a group more vulnerable to physical and social isolation, which affects their health status. Objective: This study aims to assess the health level of single female elderly in Tasikmalaya Regency using the Activity of Daily Living (ADL) instrument, and analyze the impact of socio-economic, spatial, and infrastructural factors on their health. Method: A mixed-method approach was applied, combining quantitative surveys using the Older Americans Resources and Services (OARS) ADL instrument with qualitative interviews. A total of 383 respondents were selected through cluster sampling across 39 subdistricts. Spatial analysis using GIS was employed to map health disparities by topography. Result: The findings show that most respondents fall within the “Good” and “Mildly Impaired” health categories, based on ADL scores. Elderly women in lowland areas have better ADL scores compared to those in hilly or mountainous regions due to better accessibility to healthcare facilities. The data also reveal that single elderly women are highly dependent in instrumental ADL activities such as medication management and financial handling, while they show higher independence in basic physical ADL tasks like eating, bathing, and dressing. Conclusion: The ADL instrument proves effective in evaluating the health status of elderly individuals and reflects their level of independence. Geographic and infrastructural factors play a critical role in shaping health outcomes, particularly in rural and topographically challenging areas. These results highlight the urgent need for inclusive health policies and long-term care strategies to address accessibility gaps for single elderly women in Indonesia.